The Preservation of Yogyakarta’s Cultural Heritage Through a Training Program in The Appropriate Utilization of Traditional Javanese Attire - Sa'diyah, Devi Merina Tuz; Sekti, Marita Nur; Husnawati, Husnawati; Ramadlani, Afra Shafa; Septi, Lia Eka (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
Gagrak Yogyakarta is a traditional Javanese attire in the Yogyakarta style that is rich in meaning in each of its components. It is imperative for the younger generation to acquire knowledge of the various components and meanings of traditional culture to ensure its preservation in the face of the increasingly massive cultural shifts that are occurring. The study was carried out in Yogyakarta, and it involved cultural experts. It utilized a qualitative research method with a case study design. Non-formal education is important in preserving culture, especially through training program that pass on local values, skills and traditions. The training program prioritizes skills based on local resources, in this case related to the provisions of the use of regional traditional attire called Gagrak Yogyakarta. The implementation of this training program furnishes the community with a comprehensive learning platform that meticulously examines the semantics and utilization of each component in Gagrak Yogyakarta. This training program was implemented as a component of the broader initiative aimed at safeguarding the cultural heritage of Yogyakarta, with a particular focus on the proper utilization of Yogyakarta’s traditional attire.